2014
DOI: 10.4172/2157-7110.1000346
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Antioxidant and Enzymatic Activity of Brines from Scandinavian Marinated Herring Products

Abstract: Brines generated during the last marination step in the production of marinated herring (Clupea harengus) were chemically characterized and analyzed for antioxidant and enzyme activities. The end-products were vinegar cured, spice cured and traditional barrel-salted herring with either salt or spices. The chemical characterization encompassed pH, dry matter, ash, salt, fatty acids, protein, polypeptide pattern, iron and nitrogen. The antioxidant activity was tested with three assays measuring: iron chelation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Chemical flocculation, however, renders the flocculated biomass unsuitable for further use as food or feed. To the best of our knowledge, only herring marinating brines have so far been the subject for compositional analyses (Andersen et al, 2007;Christensen et al, 2011;Gringer et al, 2014;Svensson et al, 2004;Szymczak and Kołakowski, 2012;Taheri et al, 2014;Drost et al, 2014). Thus, the total amount of biomolecules lost by leaching throughout the entire herring processing chain remains unknown.…”
Section: Herring Kep T In St Orage Water (S W) (3 % Nacl) In the Procmentioning
confidence: 97%
“…Chemical flocculation, however, renders the flocculated biomass unsuitable for further use as food or feed. To the best of our knowledge, only herring marinating brines have so far been the subject for compositional analyses (Andersen et al, 2007;Christensen et al, 2011;Gringer et al, 2014;Svensson et al, 2004;Szymczak and Kołakowski, 2012;Taheri et al, 2014;Drost et al, 2014). Thus, the total amount of biomolecules lost by leaching throughout the entire herring processing chain remains unknown.…”
Section: Herring Kep T In St Orage Water (S W) (3 % Nacl) In the Procmentioning
confidence: 97%
“…The radical-scavenging activity (RSA) was determined against ABTS radical cation (ABTS + ), according to Ginger at al. [17]. Ten µL of sample was mixed with 190 µL ABTS working solution and read after 5 min at room temperature at 734 nm.…”
Section: Antioxidant Activity Of Protein Hydrolysis Productsmentioning
confidence: 99%
“…In the case of salted whole herring, in which digestive proteases with a different specificity to cathepsins are active, the content of only a few peptides in the brines is known [17]. These brines have demonstrated significant iron(II)-chelating activity, reducing power, and radical-scavenging activity; however, in addition to the peptides, the brines contain phenolic compounds from spices, which also exhibit strong antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…This indicator was not confirmed by Stefansson and Stefansson [42] in heading herring and fillets during salting. Later results from Gringer et al [6] showed that the quantitative and qualitative composition of free amino acids in fish salted using the traditional method differed from those salted with vinegar. The traditional brine after salting contained the most lysine and threonine, while the second method contained valine and leucine.…”
Section: Cze Amino Acid Separationsmentioning
confidence: 99%
“…Amino acids have their own characteristic taste, which is why they are responsible for the specific taste of ripened salted fish meat [3][4][5]. Quantitative and qualitative composition of PHP determines the sensory quality, nutritive value, and a high content of biologically-active compounds of a ripened fish product [1,6]. During protein breakdown the texture of meat is also changed.…”
Section: Introductionmentioning
confidence: 99%